Scarring Effects of the COVID-19 Pandemic on the Italian Labour Market - Davide Fiaschi; Cristina Tealdi (Institute of Labor Economics (IZA), 2022)
The COVID-19 pandemic raised the share of inactive individuals in 2020 in Italy, mostly at the expense of permanent and fix-term employment. We document sizable asymmetric effects across categories of individuals, defined on the basis of gender, age and geographical area. In particular, the pandemic disproportionately affected females and, among those, more severely the ones living in large households in the North and Center of Italy. These findings find a rationale both in the presence of young children, which imposes strong constraints to the female labour force participation, and in the worse labour market opportunities in the South, which lead to a strong self-selection of women in the labour market. Despite the short period of observation after the burst of COVID-19 pandemic (four quarters of 2020), the identified effects appear large and persistent, rising awareness about the likely long-lasting scarring effects of the COVID-19 pandemic on the labour market choices and opportunities of Italian women.
Keywords: C18; C53; E32; E24; J6; 330; labour market flows; transition probabilities; labour market shares; female inactivity rate